Exercise training as a preventive tool for age-related disorders: a brief review (Clinics, 2013)
Aging populations are a worldwide phenomenon affecting both developed and developing countries. This issue raises serious concerns for both governments and the general population. Regular participation in physical activity and/or exercise training programs can minimize the physiological alterations that occur during aging and may contribute to improvements in health and well-being. The present review will discuss the role of regular exercise training in preventing age-related physiological decline and, consequently, associated chronic diseases. Compelling evidence that regular exercise and/or physical activity can improve quality of life, prevent or control the development of chronic disease and increase life expectancy is shown. In summary, regular exercise training and/or physical activity has an important influence on aging and may help to prevent age-related disorders.